Principales enfermedades bucodentales relacionadas con el embarazo - Silva Zavala, Heydi Dayan (2023)
ABSTRACT: Pregnancy is a natural and privileged process in a woman's life, a stage that entails a series of physical, psychological and pathological modifications that make a woman a special patient who requires differentiated care typical of the state of pregnancy. From the first weeks of pregnancy, the mother must be attended to their normal development of the new being. During pregnancy, oral health is often neglected due to both myths and the lack of knowledge about the importance of the oral cavity in the life of the human being. However, the changes in the mouth during this period are increasingly evident, so dentists and other professionals who care for pregnant women are increasingly concerned about oral health. In this way, in the present investigation, it has been proposed as objectives to identify the socioeconomic and cultural characteristics in relation to oral diseases in pregnant women, as well as to define the main oral pathologies, and to propose actions that contribute to guaranteeing the prevention of this type. of diseases. This study is descriptive, cross-sectional and documentary, based on a bibliographic review of dental articles from the main scientific journals: Google Scholar, PubMed, Scielo and Elsevier, managing to collect 63 articles that were submitted to evaluation instruments. From the main results it was possible to obtain that most of the articles were found in Google Scholar, which represents a greater influence compared to other journals based on the inclusion and exclusion criteria applied. Likewise, it was obtained that in a range of 10 years, in 2016 and 2018, more publications were registered, and inclusion of these publications had a greater quantitative approach than qualitative and mixed, with Latin American countries as the main publication residence. Keywords: oral, pregnancy, oral health, diseases, dental care, pregnancy